2015
DOI: 10.1002/art.38955
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Th17/Interleukin‐17A Immune Response in Murine Lupus Nephritis

Abstract: Objective. The CD4؉ T cell immune response plays a pivotal role in the immunopathogenesis of human and experimental lupus nephritis, but the contribution of the Th17/interleukin-17 (IL-17) immune pathway to renal tissue injury in systemic lupus erythematosus (SLE) remains to be elucidated. The aim of this study was to characterize the function of the Th17/IL-17A immune response in 2 murine models of lupus nephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 46 publications
7
37
1
Order By: Relevance
“…In previous studies, despite the fact that MDSCs from arthritic mice retain an immunosuppressive activity, the mobilized MDSCs fail to limit the immunopathology, and these cells are highly efficient in facilitating Th17 cell differentiation via IL-1β, indicating their proinflammatory nature [8,39,40]. In the present study, M-MDSCs from diseased MRL/lpr mice expressed higher levels of inflammatory cytokines (e.g.…”
Section: Discussioncontrasting
confidence: 42%
“…In previous studies, despite the fact that MDSCs from arthritic mice retain an immunosuppressive activity, the mobilized MDSCs fail to limit the immunopathology, and these cells are highly efficient in facilitating Th17 cell differentiation via IL-1β, indicating their proinflammatory nature [8,39,40]. In the present study, M-MDSCs from diseased MRL/lpr mice expressed higher levels of inflammatory cytokines (e.g.…”
Section: Discussioncontrasting
confidence: 42%
“…A recent study by Schmidt et al showed that IL-17A deficiency did not affect the morphological or functional parameters in MRL/lpr mice with lupus nephritis, nor did IL-17A neutralization affect the clinical course of nephritis in NZB/NZW mice, suggesting that the Th17/IL-17A immune response plays no major role in the immunopathogenesis of lupus nephritis in MRL/lpr and NZB/NZW mice. 19 In vitro, both autologous and allogeneic Treg cells can be satisfactorily isolated, expanded, and successfully adoptively transfused into patients with chronic GVHD. 20 However, the long-term follow-up revealed some adverse events, such as malignant melanoma or skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, in New Zealand Black (NZB)/New Zealand White (NZW) F1 mice, blockade or reduction of IFN-γ was beneficial. 8 Deletion of a regulatory element in the 3′ untranslated region of the IFN-γ gene in mice leads to congenital overexpression of IFN-γ and development of serological and cellular features characteristic of SLE. 9 Individuals treated with IFN-γ for several disorders (eg, bladder cancer, myeloproliferative disorders) developed or had potentiated autoimmune responses including SLE-like syndromes.…”
Section: Introductionmentioning
confidence: 99%